Pharmacological and polyphenolic profiles of Phyllanthus phillyreifolius var. commersonii Müll. Arg: An unexplored endemic species from Mauritius - Mahomoodally, Mohamad Fawzi; Yerlikaya, Serife; Llorent-Martínez, Eulogio J.; Uğurlu, Asli; Baloglu, Mehmet Cengiz; Altunoglu, Yasemin Celik; Mollica, Adriano; Dardenne, Kurty Kersley; Aumeeruddy, Muhammad Zakariyyah; Puchooa, Daneshwar; Zengin, Gokhan (Elsevier BV, 2019)
Phyllanthus phillyreifolius var. commersonii Müll. Arg is an endemic plant of Mauritius. To date, no study has been performed concerning its polyphenolic profile and pharmacological properties. In this study, a decoction (water), ethyl acetate and methanol extracts of the aerial parts of P. phillyreifolius, obtained from different extraction procedures (maceration and Soxhlet), were studied for antibacterial, antioxidant, anticancer, and enzyme inhibitory properties along with their polyphenolic profile. The ethyl acetate macerated extract showed high antibacterial activity against B. cereus (MIC = 0.293 mg/mL) and E. coli (MIC = 0.417 mg/mL) while S. epidermidis was most susceptible to the ethyl acetate-Soxhlet extract (MIC = 0.521 mg/mL). The methanol-Soxhlet extract displayed the most potent cupric and ferric reducing power, and metal chelating effect, while the macerated methanolic extract was the most effective DPPH and ABTS scavenger, and BChE inhibitor. Only the ethyl acetate-Soxhlet extract exhibited α-glucosidase inhibition. All extracts exhibited a strong anti-tyrosinase activity, which was further investigated by molecular docking and molecular dynamic. After 48 h exposure to the extracts for HeLa cell lines, the ethyl acetate-Soxhlet extract showed the highest inhibition (IC50 = 533.1 μg/mL) while the decoction extract was more cytotoxic to MDA-MB-231 cells (IC50 = 337.4 μg/mL). Treatment of cancer cell lines with all P. phillyreifolius extracts resulted in a time-dependent reduction of cell viability for HeLa and dose-and time-dependent reduction for MDA-MB-231. Gene expression ratio of Bcl-2 to Bax was higher for all Soxhlet-extracts. Total phenolics (TPC) and flavonoids (TFC) content were highest in the decoction and methanol-Soxhlet extract, respectively (122.43 mg GAE/g extract and 31.28 mg RE/g extract, respectively). The extracts were abundant in ellagitannins, although phenolic acids and flavonoids were also detected. Granatin B was detected for the first time in Phyllanthus species. Overall, the aerial parts of P. phillyreifolius exemplify a potent reservoir of bioactive phytochemicals for therapeutic applications.
Keywords: Antibacterial; Anticancer; Antioxidant; Enzyme inhibition; Phyllanthus phillyreifolius; Polyphenolic; Food Science; Cell Survival; Phytochemicals; Antineoplastic Agents; Microbial Sensitivity Tests; Molecular Dynamics Simulation; Antioxidants; Phyllanthus phillyreifolius; Phenols; Humans; Enzyme Inhibitors; Flavonoids; Bacteria; Monophenol Monooxygenase; Plant Extracts; Hydrolyzable Tannins; Anti-Bacterial Agents; Antibacterial; Molecular Docking Simulation; Enzyme inhibition; Phyllanthus; Anticancer; Polyphenolic; Mauritius; Antioxidant; HeLa Cells